Digital Fairness and the Burden of Proof - P. Rott (Journal of Consumer Policy, 2025)
Digital infrastructures, such as online platforms, and digital services, such as scoring, and the algorithms behind them, have often been described as a "black box." This is a problem for consumers and consumer organizations that wish to enforce their individual rights or collective remedies in civil law litigation. The reason is that traditionally, the burden of proof is normally on the claimant, who has to prove those elements of a legal provision that act in their favour, whereas the burden of proof for defences is normally on the defendant. Burden of proof has therefore been identified as a major obstacle in the fight against digital unfairness. This means, at the same time, that the important element of private enforcement is insufficient, which hampers the effectiveness of EU consumer law in general. On this background, this article discusses, after some preliminary remarks addressing the scope of the problem, (1) to what extent EU law already requires alleviations of the burden of proof in litigation around unfair digital commercial practices in national courts and (2) how a tailor-made regime of specific provisions related to the burden of proof could, or should, be designed.
Keywords: 650; Burden of proof; Digital services; Product Liability Directive; Unfair Commercial Practices Directive